Revision of the family Carabodidae (Acari, Oribatida) XII. Yoshiobodes camerunensis sp. n. and Rugocepheus costaricensis sp. n. - Fernandez, Nestor; Theron, Pieter Daniel; Leiva, Sergio Dante; Tiedt, Louwrens (Pensoft Publishers, 2019)
Yoshiobodes camerunensis sp. n., collected in Cameroon, is the first species of this genus reported from the Afrotropical region. Diagnostic characters include lamellae terminating in a bridge and not in lamellar tips; cup-shaped bothridia, bothridial ring present; rostral setae cochleariform, smooth; lamellar setae slightly lanceolate, barbate; fifteen pairs of notogastral setae; c3 lanceolate, rounded end, with longitudinal shallow grooves; other notogastral setae curved lanceolate-cochleariform. Rugocepheus costaricensis sp. n. is the third species of the genus to be described, and the first collected outside the African region. Prodorsum presents a Y-shaped structure; elevated interlamellar process, superior flat zone; lamellae lacking lamellar tips; fourteen pairs of notogastral setae; four notogastral furrows, and an unpaired elevated central area devoid of setae. Both species are described and illustrated based on adult specimens, studied by means of optical and SEM microscopy.